User QoS enhanced web service composition framework in cloud platforms. (1st January 2013) - Xiao, Peng; Liu, Dongbo
Recently, deploying web services in cloud platforms has become a popular issue that attracts plenty of attentions. Unlike typical service platforms, cloud system provides an elastic infrastructure for service provision and security isolation. As a result, the service composition in a cloud platform becomes more flexible and negotiable, especially when users have multiple QoS constraints with various weights. To address the problem of service composition with multiple QoS constraints in cloud systems, we propose a QoS-enhanced web service composition framework, in which evolution strategy is applied to solve the optimal service composition which is formulated as multiple choice multiple dimension knapsack problem. Based on the proposed service composition, a QoS negation mechanism is also designed with aiming to adapt the dynamical and elastic cloud environments. Extensive experiments are conducted to investigate the effectiveness of the proposed framework, and the results show that it can significantly reduce the costs of large-scale service-based application in terms of various QoS metrics.